Understanding healing : meditative reflections on deepening medicine through spiritual science : thirteen lectures and a meeting held in Dornach between January and April 1924 : first newsletter of the medical section, March 1924 /: meditative reflections on deepening medicine through spiritual science : thirteen lectures and a meeting held in Dornach between January and April 1924 : first newsletter of the medical section, March 1924. (2013) - Steiner, Rudolf, 1861-1925
No abstract available